2018
DOI: 10.16956/jes.2018.18.2.98
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the 2017 TNM Classification of Thyroid Carcinoma

Abstract: The objective of this article is to detail the 2017 tumor-node-metastasis (TNM) staging criteria for thyroid cancer. The literature presents only few contributions, with controversial results, about comparison between previous and the new TNM systems. The 2017 TNM classification categorizes either thyroid carcinomas only limited to the gland either carcinomas macroscopically infiltrating into defined anatomical structures. The "minimal extrathyroid spread" into the perithyroidal adipose tissue no longer appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Invasion of strap muscle in any degree may not have significant survival impact due to the relative complexity of posterior anatomical structures such as trachea, recurrent laryngeal nerve, and prevertebral fascia. Critical laryngotracheal structure invasion leads to a higher possibility of incomplete resection and therefore to higher clinical recurrence and poorer prognosis 9 . On the other hand, strap muscles can be relatively easily resected in the presence of tumor invasion 13 , 22 , accounting for their lack of significant impact on DSS.…”
Section: Discussionmentioning
confidence: 99%
“…Invasion of strap muscle in any degree may not have significant survival impact due to the relative complexity of posterior anatomical structures such as trachea, recurrent laryngeal nerve, and prevertebral fascia. Critical laryngotracheal structure invasion leads to a higher possibility of incomplete resection and therefore to higher clinical recurrence and poorer prognosis 9 . On the other hand, strap muscles can be relatively easily resected in the presence of tumor invasion 13 , 22 , accounting for their lack of significant impact on DSS.…”
Section: Discussionmentioning
confidence: 99%
“…Suspected anterior gross ETE indicated that anterior strap muscle invasion was suspected on US. Gross strap muscle invasion (T3b) is associated with a higher risk of positive resection margins, larger tumor size, higher recurrence rate, and lower disease survival rate (17)(18)(19). Therefore, when anterior gross ETE is suspected, both surgeons and endocrinologists recommend TT in many cases.…”
Section: Discussionmentioning
confidence: 99%